Problems of adaptation of foreign applicants to study in the educational program "Automotive Engineering" - Novina, N.; Новіна, Наталія Нарсенівна (Харківський національний автомобільно-дорожній університет, 2015)
The issue of student adaptation to studying at higher education institutions in Ukraine is extremely relevant, especially in the context of globalization, the active internationalization of the educational space, and the continuous increase in the number of international students choosing Ukraine for their higher education. Adaptation is a complex, multifactorial process that includes not only academic but also social, psychological, and cultural components, all of which are closely interrelated and mutually influential. Particular attention should be given to the effective integration of international students into the learning environment of Ukraine’s technical universities, where the educational process is characterized by a high level of intellectual demand, specialized terminology, and the need for advanced analytical skills. At the same time, it is noted that the academic community has paid insufficient attention to the impact of cultural distance on the adaptation process. The article emphasizes the importance of a thorough analysis of the adaptation process in the context of cultural differences, as the cultural distance between a student’s country of origin and the Ukrainian cultural environment can significantly influence the speed, effectiveness, and completeness of their integration into the academic and social setting of the university. Purpose. To determine the level of adaptation of international students enrolled in the "Automotive Engineering" program depending on cultural distance and to identify factors that facilitate or hinder this process. Methodology. The study involved 60 international students from Turkmenistan, Azerbaijan, Morocco, Tunisia, Cameroon, and Nigeria. The research methods included surveys (including the International Student Adaptation Scale), observations, interviews, and analysis of academic performance and extracurricular participation. The data were analyzed using both quantitative (mean, variance, correlations) and qualitative methods. Results. It was found that students from culturally closer regions (Group 1) were the most adapted, while those from countries with greater cultural distance (Group 3) experienced significant difficulties. The main barriers were language challenges, culture shock, differences in academic expectations, and psychological pressure. Practical value. The study developed recommendations to improve language training, cultural integration, and academic support, which can be implemented by higher education institutions to ensure more effective adaptation of international students and reduce academic attrition rates.
Проблеми адаптації іноземних здобувачів до навчання за освітньої програмою "Автомобілебудування"
Keywords: foreign applicants; adaptation; culture shock; language barrier; cultural distance; motivation; іноземні здобувачі; адаптація; культурний шок; мовний бар'єр; культурна дистанція; 378.147; 10.30977/AT.2219-8342.2025.56.0.05